Low-shrinkage PBT (polybutylene terephthalate) composite material as well as preparation method and application thereof
By refining the composite material formulation and preparation process, a low-shrinkage PBT composite material was prepared, which solved the problem of PBT material aging under long-term outdoor exposure, improved its anti-aging performance, and made it suitable for outdoor equipment protection.
Patent Information
- Application Number
- CN202511051334.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-11
AI Technical Summary
PBT materials are prone to aging when exposed to the outdoors for extended periods, losing their protective effect and leading to equipment damage.
Low-shrinkage PBT composite materials are prepared using a specific process through a combination of composite material formulations, including PBT, PETG, PET, fiber fillers, antioxidants, flame retardants, release agents, and stabilizers, thereby enhancing their anti-aging properties.
PBT composite materials with low shrinkage properties maintain good anti-aging effects during long-term outdoor use, making them suitable for outdoor equipment protection.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application belongs to the field of polymer materials technology, specifically relating to a low-shrinkage PBT composite material, its preparation method, and its application. Background Technology
[0002] PBT (polybutylene terephthalate) is a semi-crystalline linear saturated polyester that is widely used in outdoor materials, electronics, automotive industry, machinery, instruments and meters, and household appliances due to its excellent heat resistance, chemical resistance, electrical properties and processing properties.
[0003] However, when PBT materials are used in outdoor facilities, they may age unnoticed due to prolonged lack of maintenance. For example, when used as protective covers for outdoor equipment, they are prone to aging due to long-term exposure to sunlight. Once aged, the PBT material loses its protective effect, eventually exposing the equipment and causing damage.
[0004] Therefore, it is necessary to develop a PBT composite material with low shrinkage properties that can withstand long-term outdoor exposure. Summary of the Invention
[0005] The purpose of this application is to overcome the shortcomings of the prior art and provide a low-shrinkage PBT composite material, its preparation method, and its application, specifically adopting the following technical solution: First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: PBT 73-128 parts; PETG 12-38 parts; PET 3-19 parts; Fiber filler 21-35 parts; First additive 12-27 parts; Second additive 21-38 parts; The raw materials for the first additive include antioxidants and β-cyclodextrin; The raw materials for the second additive include flame retardant, release agent and stabilizer, wherein the mass ratio of flame retardant, release agent and stabilizer is (5-11):(1-2):(1-2).
[0006] The low-shrinkage PBT composite material provided in this application achieves its low-shrinkage characteristic through the combination of various raw materials and the addition of fiber fillers. Furthermore, the combination of various substances in the raw materials creates an excellent synergistic effect. Specifically, the first and second additives, made from specific raw materials and processed using specific techniques, synergize with the PBT and other raw materials provided in this application, thereby enhancing the anti-aging effect of the PBT composite material.
[0007] In some specific implementations, the raw materials of the low-shrinkage PBT composite material also include 1-15 parts of dye by weight; by adding dye, the PBT composite material provided in this application can provide more color choices in actual use, thereby having a better visual effect in specific application scenarios.
[0008] In some specific implementations, the antioxidant includes at least one of butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT). More preferably, the antioxidant is composed of BHA and BHT in a mass ratio of 1:1, which is more effective in the low-shrinkage PBT composite material system provided in this application.
[0009] In some specific implementations, the preparation method of the first additive includes: dissolving β-cyclodextrin in a 30%-60% (w / w) aqueous ethanol solution to prepare a saturated β-cyclodextrin solution; dissolving an antioxidant in anhydrous ethanol to prepare a saturated antioxidant solution; heating the saturated β-cyclodextrin solution to 45℃-50℃, and while stirring, mixing the saturated antioxidant solution with the saturated β-cyclodextrin solution, stirring continuously for 2-5 hours, then stopping the stirring, allowing it to cool naturally, and filtering after cooling to obtain the first additive.
[0010] In some specific embodiments, the flame retardants include brominated flame retardants, halogen-phosphorus synergistic flame retardants, and phosphorus-based flame retardants. In a preferred embodiment, the selected flame retardant is prepared by mixing brominated flame retardants, halogen-phosphorus synergistic flame retardants, and phosphorus-based flame retardants in a mass ratio of 2:3:1. This specific combination of flame retardants in this ratio can work synergistically with other components in the low-shrinkage PBT composite material provided in this application to achieve the best technical effect.
[0011] In some specific implementations, the release agent includes at least one of paraffin wax, silicone oil, talc, mica, zinc stearate, and phosphate ester; wherein the addition of the release agent can more effectively enable the low-shrinkage PBT composite material provided in this application to be more easily removed from the mold after molding in the specific mold during the specific use process, avoiding adhesion.
[0012] In some specific implementations, stabilizers include benzotriazole stabilizers.
[0013] In some specific implementations, the preparation method of the second additive includes: dissolving the flame retardant in a polyol to prepare a saturated flame retardant solution, then adding a polyisocyanate, heating to 50℃-70℃, reacting for 3h-8h, then separating to obtain the first solid, and mixing the first solid with a release agent and a stabilizer to obtain the second additive.
[0014] Secondly, this application also provides a method for preparing the above-mentioned low-shrinkage PBT composite material, comprising the following steps: mixing PBT, PETG, PET and a second additive, then performing melt extrusion at 190℃-270℃ using a twin-screw extruder, and adding fiber filler and a first additive at the side feed port.
[0015] Finally, this application also provides an application of the above-mentioned low-shrinkage PBT composite material in a protective cover.
[0016] The beneficial effects of this application are as follows: Through the compound formulation of the components, the PBT composite material provided by this application has low shrinkage characteristics and excellent anti-aging effect, thereby making the products made of the PBT composite material provided by this application more suitable for long-term outdoor use. Detailed Implementation
[0017] The following will provide a clear and complete description of the concept and technical effects of this application in conjunction with embodiments, so as to fully understand the purpose, solution and effects of this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.
[0018] Example 1 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 15 parts first additive; 28 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw materials for the first additive are antioxidant and β-cyclodextrin; the antioxidant is butylated hydroxyanisole and butylated hydroxytoluene in a mass ratio of 1:1.
[0019] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0020] The preparation method of the first additive is as follows: β-cyclodextrin is dissolved in a 45% concentration ethanol aqueous solution to prepare a β-cyclodextrin saturated solution; an antioxidant is dissolved in anhydrous ethanol to prepare an antioxidant saturated solution; the β-cyclodextrin saturated solution is heated to 50°C, and while stirring, the antioxidant saturated solution and the β-cyclodextrin saturated solution are mixed evenly and stirred continuously for 4 hours. Then, stirring is stopped, and the mixture is allowed to cool naturally. After cooling, the mixture is filtered to obtain the first additive.
[0021] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0022] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0023] Example 2 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 117 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 15 parts first additive; 28 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw materials for the first additive are antioxidant and β-cyclodextrin; the antioxidant is butylated hydroxyanisole and butylated hydroxytoluene in a mass ratio of 1:1.
[0024] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0025] The preparation method of the first additive is as follows: β-cyclodextrin is dissolved in a 45% concentration ethanol aqueous solution to prepare a β-cyclodextrin saturated solution; an antioxidant is dissolved in anhydrous ethanol to prepare an antioxidant saturated solution; the β-cyclodextrin saturated solution is heated to 50°C, and while stirring, the antioxidant saturated solution and the β-cyclodextrin saturated solution are mixed evenly and stirred continuously for 4 hours. Then, stirring is stopped, and the mixture is allowed to cool naturally. After cooling, the mixture is filtered to obtain the first additive.
[0026] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0027] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0028] Example 3 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 15 parts first additive; 28 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw materials for the first additive are antioxidant and β-cyclodextrin; the antioxidant is butylated hydroxyanisole.
[0029] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0030] The preparation method of the first additive is as follows: β-cyclodextrin is dissolved in a 45% concentration ethanol aqueous solution to prepare a β-cyclodextrin saturated solution; an antioxidant is dissolved in anhydrous ethanol to prepare an antioxidant saturated solution; the β-cyclodextrin saturated solution is heated to 50°C, and while stirring, the antioxidant saturated solution and the β-cyclodextrin saturated solution are mixed evenly and stirred continuously for 4 hours. Then, stirring is stopped, and the mixture is allowed to cool naturally. After cooling, the mixture is filtered to obtain the first additive.
[0031] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0032] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0033] Example 4 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 27 parts first additive; 28 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw materials for the first additive are antioxidant and β-cyclodextrin; the antioxidant is butylated hydroxyanisole and butylated hydroxytoluene in a mass ratio of 1:1.
[0034] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0035] The preparation method of the first additive is as follows: β-cyclodextrin is dissolved in a 45% concentration ethanol aqueous solution to prepare a β-cyclodextrin saturated solution; an antioxidant is dissolved in anhydrous ethanol to prepare an antioxidant saturated solution; the β-cyclodextrin saturated solution is heated to 50°C, and while stirring, the antioxidant saturated solution and the β-cyclodextrin saturated solution are mixed evenly and stirred continuously for 4 hours. Then, stirring is stopped, and the mixture is allowed to cool naturally. After cooling, the mixture is filtered to obtain the first additive.
[0036] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0037] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0038] Example 5 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 27 parts first additive; 38 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw materials for the first additive are antioxidant and β-cyclodextrin; the antioxidant is butylated hydroxyanisole and butylated hydroxytoluene in a mass ratio of 1:1.
[0039] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0040] The preparation method of the first additive is as follows: β-cyclodextrin is dissolved in a 45% concentration ethanol aqueous solution to prepare a β-cyclodextrin saturated solution; an antioxidant is dissolved in anhydrous ethanol to prepare an antioxidant saturated solution; the β-cyclodextrin saturated solution is heated to 50°C, and while stirring, the antioxidant saturated solution and the β-cyclodextrin saturated solution are mixed evenly and stirred continuously for 4 hours. Then, stirring is stopped, and the mixture is allowed to cool naturally. After cooling, the mixture is filtered to obtain the first additive.
[0041] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0042] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0043] Comparative Example 1 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 28 parts secondary additive; 5 parts white dye; The fiber filler is glass fiber. The raw materials for the second additive are flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1. The mold release agent is paraffin wax, and the stabilizer is a benzotriazole stabilizer (UV-327).
[0044] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0045] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0046] Comparative Example 2 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 15 parts first additive; 28 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw materials for the first additive are antioxidant and β-cyclodextrin; the antioxidant is butylated hydroxyanisole and butylated hydroxytoluene in a mass ratio of 1:1.
[0047] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0048] The preparation method of the first additive includes: dissolving β-cyclodextrin in a 45% aqueous ethanol solution to prepare a saturated β-cyclodextrin solution; dissolving an antioxidant in anhydrous ethanol to prepare a saturated antioxidant solution; heating the saturated β-cyclodextrin solution to 50°C; while stirring, mixing the saturated antioxidant solution with the saturated β-cyclodextrin solution; stirring continuously for 4 hours; then stopping the stirring; allowing it to cool naturally; and filtering after cooling to obtain the first additive.
[0049] The preparation method of the second additive includes: mixing the flame retardant with the release agent and the stabilizer to obtain the second additive.
[0050] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0051] Comparative Example 3 First, this application provides a low-shrinkage PBT composite material, which, by weight, comprises the following raw materials: 80 parts PBT; 19 parts PETG; 11 parts PET; 28 parts fiber filler; 15 parts first additive; 28 parts second additive; 5 parts white dye; The fiber filler is glass fiber, and the raw material for the first additive is an antioxidant; the antioxidant is butylated hydroxyanisole and butylated hydroxytoluene in a mass ratio of 1:1.
[0052] The second additive consists of flame retardant, mold release agent, and stabilizer, with a mass ratio of 9:1:1. The flame retardant is prepared by mixing a brominated flame retardant (decabromodiphenyl ether flame retardant), a halogen-phosphorus synergistic flame retardant (TCEP), and a phosphorus flame retardant (triphenyl phosphate flame retardant) in a mass ratio of 2:3:1; the mold release agent is paraffin wax; and the stabilizer is a benzotriazole stabilizer (UV-327).
[0053] The preparation method of the second additive is as follows: the flame retardant is dissolved in ethanol to prepare a saturated flame retardant solution, then polyisocyanate is added, the temperature is raised to 60°C, and the reaction is carried out for 5 hours. The first solid is then separated, and the first solid is mixed with the release agent and stabilizer to obtain the second additive.
[0054] Secondly, the specific preparation method of the above-mentioned low-shrinkage PBT composite material includes the following steps: mixing the above-mentioned PBT, PETG, PET and the second additive, then using a twin-screw extruder to perform melt extrusion at 260°C, and adding fiber filler and the first additive at the side feed port to obtain PBT composite material particles.
[0055] Experiments and Results Particles of the PBT composite materials obtained in Examples 1-5 and Comparative Examples 1-3 were injection molded in an injection molding machine at 240°C. Strip-shaped test samples were prepared according to the relevant requirements of each standard for testing, and performance tests were conducted according to the relevant standards, as follows: Tensile strength test: The test was conducted in accordance with ASTM D638-22 Standard Test Method for Tensile Properties of Plastics. This test method involves determining the tensile properties of unreinforced and reinforced plastics in the form of standard dumbbell-shaped specimens under specified pretreatment, temperature, humidity and testing machine speed conditions. Specific data are shown in Table 1.
[0056] Flame retardant performance test: The test was conducted in accordance with UL 94 Test for Flammability of Plastic Materials for Equipment and Appliance Components. This test method is used to evaluate the extinguishing ability of the material after it is re-ignited. Specific data are shown in Table 1.
[0057] Tensile strength and aging resistance test: The test was conducted in accordance with GB / T 16422.2-2022 Plastics Laboratory Light Source Exposure Test Method Part 2: Xenon Arc Lamp. This test uses a xenon arc lamp with a suitable filter as the light source to simulate the spectral irradiance in the ultraviolet and visible regions of the total solar radiation spectrum, thereby subjecting the sample to a high-intensity aging test at a temperature of 65℃ and RH of 80% for 2000 hours. The tensile strength after aging was recorded, and the specific data are shown in Table 1.
[0058] Table 1 As can be seen from Table 1, the low-shrinkage PBT composite material provided in this application still retains high tensile strength after aging, indicating that the low-shrinkage PBT composite material provided in this application has strong aging resistance and is suitable for manufacturing various products for outdoor use.
[0059] Impact strength test: The test was conducted in accordance with GB / T 1843-2008, "Determination of Impact Strength of Plastic Cantilever Beams." This test method utilizes the following principle to assess the impact strength of the specimen: a pendulum of known energy impacts the specimen, which is supported as a vertical cantilever beam, in a single strike, and the energy absorbed upon specimen failure is measured. The distance from the impact line to the specimen clamp is fixed; for notched specimens, the distance from the impact line to the center line of the notch is also fixed. Specific test data are shown in Table 2.
[0060] Impact strength and aging resistance test: The test was conducted in accordance with GB / T 16422.2-2022 Plastics Laboratory Light Source Exposure Test Method Part 2: Xenon Arc Lamp. This test uses a xenon arc lamp with a suitable filter as the light source to simulate the spectral irradiance in the ultraviolet and visible regions of the total solar radiation spectrum, thereby subjecting the sample to a high-intensity aging test at 65℃ and RH 80% for 2000 hours. The impact strength after aging was recorded, and the specific data are shown in Table 2.
[0061] Table 2 As can be seen from Table 2, the low-shrinkage PBT composite material provided in this application can still maintain high impact strength after aging, indicating that the low-shrinkage PBT composite material provided in this application has strong anti-aging properties and is more suitable for outdoor use.
[0062] Although the description of this application has been quite detailed and particularly focused on several of the described embodiments, it is not intended to limit itself to any of these details or embodiments or any particular embodiment. Rather, it should be considered as providing a broad possible interpretation of the claims by referring to the appended claims and taking into account the prior art, thereby effectively covering the intended scope of this application. Furthermore, the foregoing description of this application with respect to embodiments foreseeable by the applicant is intended to provide a useful description, and non-substantial modifications to this application that have not yet been foreseen may still represent equivalent modifications.
Claims
1. A low-shrinkage PBT composite material, characterized in that, By weight, the raw materials include: PBT 73-128 parts; PETG 12-38 parts; PET 3-19 parts; Fiber filler 21-35 parts; First additive 12-27 parts; Second additive 21-38 parts; The raw materials for the first additive include antioxidants and β-cyclodextrin; The raw materials of the second additive include flame retardant, mold release agent and stabilizer, and the mass ratio of the flame retardant, the mold release agent and the stabilizer is (5-11):(1-2):(1-2).
2. The low-shrinkage PBT composite material according to claim 1, characterized in that, The raw materials for the low-shrinkage PBT composite material also include 1-15 parts of dye by weight.
3. The low-shrinkage PBT composite material according to claim 1, characterized in that, The antioxidant includes at least one of butylated hydroxyanisole and butylated hydroxytoluene.
4. The low-shrinkage PBT composite material according to claim 3, characterized in that, The preparation method of the first additive includes: dissolving the β-cyclodextrin in a 30%-60% (w / w) aqueous ethanol solution to prepare a saturated β-cyclodextrin solution; dissolving the antioxidant in anhydrous ethanol to prepare a saturated antioxidant solution; heating the saturated β-cyclodextrin solution to 45°C-50°C, and while stirring, mixing the saturated antioxidant solution with the saturated β-cyclodextrin solution, stirring continuously for 2-5 hours, then stopping the stirring, allowing it to cool naturally, and filtering after cooling to obtain the first additive.
5. The low-shrinkage PBT composite material according to claim 1, characterized in that, The flame retardants include brominated flame retardants, halogen-phosphorus synergistic flame retardants, and phosphorus-based flame retardants.
6. The low-shrinkage PBT composite material according to claim 1, characterized in that, The release agent includes at least one of paraffin wax, silicone oil, talc, mica, zinc stearate, and phosphate ester.
7. The low-shrinkage PBT composite material according to claim 1, characterized in that, The stabilizers include benzotriazole stabilizers.
8. The low-shrinkage PBT composite material according to claim 1, characterized in that, The preparation method of the second additive includes: dissolving the flame retardant in a polyol to prepare a saturated flame retardant solution, then adding a polyisocyanate, heating to 50℃-70℃, reacting for 3h-8h, then separating to obtain a first solid, and mixing the first solid with the release agent and the stabilizer to obtain the second additive.
9. A method for preparing a low-shrinkage PBT composite material according to any one of claims 1-8, characterized in that, The process includes the following steps: mixing the PBT, PETG, PET and the second additive, then performing melt extrusion at 190°C-270°C using a twin-screw extruder, and adding the fiber filler and the first additive at the side feed port.
10. The application of a low-shrinkage PBT composite material according to any one of claims 1 to 8 in a protective cover.